The use of response surface analysis in obtaining maximum profit in oil palm industry - Khamis, Azme; Ismail, Zuhaimy; Haron, Khalid; Mohammed, Ahmad Tarmizi (Songkla University, 2006)

(untitled)
This study was conducted to show how to use Response Surface Analysis in obtaining the optimum level of fertilizer needs by oil palm. The ridge analysis was proposed to overcome the saddle point problem. Data from Malaysian Palm Oil Board database was analyzed. The fertilizers considered are N, P, K and Mg. The results from ridge analysis provided several alternatives of the fertilizer combination. Profit analysis was then applied to determine the best combination of fertilizers needed by the oil palm in order to generate maximum profit. It is found that N and K fertilizers were the important fertilizers required by the oil palm. It is also found that the N and K nutrient concentrations of the foliar nutrient composition were higher compared to other nutrients. Three different stations were considered and it was found that the fertilizers needed by the oil palm and foliar nutrient composition were different at the different type of soil series.